Quantitative and qualitative analyses of Islamic Banks' pricing practices: Factors explaining the performance - Nor F.M.; Shaharuddin A.; Marzuki A.; Nawai N.; Zainuddin W.Z. (Islamic Bank Training and Research Academy, 2024)
Indexed by SCOPUS